Revealing the fast and durable Na⁺ insertion reactions in a layered Na₃Fe₃(PO₄)₄ anode for aqueous Na-ion batteries - Qiu, Shen (2022)
Aqueous sodium-ion batteries represent a promising approach for stationary energy storage; however, the lack of appropriate anode materials has substantially retarded their development. Herein, we demonstrated an iron-based phosphate material of Na3Fe3(PO4)4 as an inexpensive and efficacious anode alternative. While the Fe3+/Fe2+ redox couple renders a two-Na-insertion reaction with desirable potentials, its unique layered structure further facilitates the Na-insertion kinetics and reversibility. Consequently, this electrode exhibits an appealing Na-insertion performance, with a reversible capacity of ∼83 mAh g-1, suitable anode potential of -0.4 V vs Ag/AgCl, excellent rate capability of 200 C, and outstanding cycling of 6000 cycles. Utilizing operando synchrotron X-ray diffraction and X-ray absorption spectroscopy, we revealed the structural evolution of the Na3Fe3(PO4)4 anode during the two-electron reaction, where the extremely small volume expansion (∼3%) enables its fast-charging and long-cycling capability. Our work suggests new considerations of developing versatile iron phosphate compounds as appealing anode materials for energy storage in aqueous electrolytes.